KOMPUTERISASI KEBUTUHAN DAN PREDIKSI PENYIMPANAN DOKUMEN REKAM MEDIS (STUDI KASUS:RSIA AMANAH IBU SURAKARTA) - Wahyuningsih Nugraheni, Sri; -, Nurhayati (LP2M Universitas Nurdin Hamzah, 2020)
The hospital keeps medical record documents in the filling section on both the insulated shelf and the roll o’pack. The hospital needs to procure medical record document shelves, taking into account many aspects. The Amanah Mother Hospital in Surakarta has never calculated the need for shelves for storing medical records, the increase in the number of patient visits is not balanced with the addition of storage. The purpose of this study is to build computer applications to calculate the needs and predictions of storing medical record documents. Research methods include (1) Planning, (2) Data Collection & Requirement Analysis, (3) Designing, (4) Making, (5) Testing & Evaluating (6) Using the system. This research produces a computer application that is able to calculate the storage needs and predictions of storage of medical record documents for the next 5 years based on the number of new patient visits in the last 3 years, the size of the rack dimensions and the average thickness of medical record documents. The results of the needs report and the prediction of the storage of medical records must be considered by the hospital for procurement of shelves. Conclusion computer applications have been able to help hospitals to calculate the needs of storing medical record documents and predict the need for efficiently storing medical record documents.